The Rowan Tree Church 23rd Annual Report, Hallows 2004 ce-Hallows 2005 ce. - Rowan Tree Church (Kirkland: WA: Rowan Tree Church, 2005)
The twenty-third annual report reflects on the last two years beginning with a return to the Church’s roots and last year’s planting of seeds in order to insure a strong foundation and future. This year’s annual report uses the analogy of “rising of the sap” as the authors record the new initiatives and growth of the Church. Included in this narrative is a reflection of the economy and how it has impacted the finances of the Church. This report also announces the demise of The Littlest Unicorn, which always had low subscribers, but was another victim of the combined economy and internet. One initiative of note is the increased presence on Wiccan sites, particularly to attract more members.
This digital asset was created from the original digital scans by Rev. Paul V. Beyerl and provided to the Valdosta State University, Archives & Special Collections to be part of their Rowan Tree Church Periodicals Collection of the New Age Movements, Occultism, and Spiritualism Research Library. The Rowan Tree Church is an earth-based religion founded by Rev. Paul Beyerl, a Third Degree Initiate in the Alexandrian Tradition of Wicca, and incorporated on February 4, 1980 in Minneapolis, Minnesota. The church is now based in Kirkland, Washington with many communities throughout the United States and Canada. The roots of the Church extend back to 1976 which Rev. Beyerl began teaching Wicca, Astrology, and Herbalism out of his home. The Church's religion, The Tradition of Lothloriën, embraces inclusiveness and accepts all people regardless of faith, sexual orientation, race, or gender, a noted departure from early Alexandrian Wicca. The Tradition has elements of Herbalism, Astrology and Tibetan Buddhism in its structure, and is deeply rooted in its Mystery School, an in-depth study program that leads to Ordination, and the Hermit's Grove, its educational and publishing entity. Noted publications are The Unicorn, The Littlest Unicorn for children, and The Hermit’s Lantern.
Keywords: Rowan Tree Church--History; Beyerl, Paul V., Rev., 1945-; Rowan Tree Church--Administration; Rowan Tree Church--Appropriations and expenditures; Internet; Mystery School of Lothloriën; Lothloriën (Wiccan sect); Rowan Tree Church. Library; Hermit's Grove (Rowan Tree Church); Wicca--Study and teaching; Church work with prisoners; Prisoners--Religious life; Galadhrim Society of Unicorns; Prison Outreach Program; Annual reports